John Updike and the Funny Theologian - McTavish, John (Theology today, 1992)
“Updike doesn't preach. He tells realistic stories with symbolic and theological overtones that, in effect, invite us to enter the discussion ourselves. Here we are invited to consider the goodness of our relationship with God. God's partnership with us in the covenant of grace disclosed in Christ does not, as has been said, solve our many problems. Yet, within our blood-soaked world, it does give us a place to stand. Only goodness lives. But it does live. God is God and may be trusted to fill our lives with radiance and the world with joy.”